World Economy Winter 2018 - Slower growth in the world economy - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Saskia Mösle; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2018)
World economic growth is moderating accompanied by a broad-based deterioration in economic sentiment. Following a temporary pick up in the second quarter, global activity slowed down significantly in the third quarter and sentiment indicators point towards a further deceleration towards the end of the year. Increased uncertainty from global trade conflicts and the tightening of monetary policy in the US that has put emerging economies under pressure have likely contributed to this development. We expect the global economy to expand at a rate of 3.7 percent this year, followed by 3.4 next year. This is a slight downward revision for 2018 and 2019 by 0.1 percentage points compared to our September forecast. For 2020, we continue to expect world production to increase by 3.4 percent. The escalation of trade conflicts, the possibility of a 'hard Brexit', doubts about the sustainability of Italian public debt, and a delay of reforms in France pose downside risks to our outlook. – – Die Weltkonjunktur hat im Verlauf des Jahres 2018 an Fahrt verloren. Die wirtschaftliche Stimmung hat sich nahezu überall deutlich eingetrübt. Hierzu hat neben einer Verunsicherung durch zunehmende handelspolitische Konflikte die Straffung der Geldpolitik in den Vereinigten Staaten beigetragen, in deren Folge es zu einem Umschwung bei den internationalen Kapitalströmen kam, der die wirtschaftliche Expansion in den Schwellenländern bremst. Die Weltproduktion, gerechnet auf Basis von Kaufkraftparitäten, wird in diesem Jahr wie im vergangenen Jahr um 3,7 Prozent zunehmen. Im kommenden Jahr dürfte die Zuwachsrate auf 3,4 Prozent zurückgehen. Wir haben unsere Prognose vom September damit für 2018 und 2019 nochmals leicht - um jeweils 0,1 Prozentpunkte - reduziert. Für 2020 erwarten wir unverändert einen Zuwachs um abermals 3,4 Prozent. Risiken bestehen insbesondere in einer weiteren Verschärfung der Handelskonflikte. In Europa könnten Sorgen um die Schuldentragfähigkeit in Italien, die Verzögerung von Reformen in Frankreich und nicht zuletzt ein möglicher ungeordneter Brexit dazu führen, dass sich die Konjunktur schwächer entwickelt als erwartet.
Keywords: 330; advanced economies; emerging economies; monetary policy; global outlook; fiscal policy; trade conflict